2014
DOI: 10.15640/jeds.v2n4a10
|View full text |Cite
|
Sign up to set email alerts
|

The Egalitarian Impact of Aid on Some Latin American Countries

Abstract: Literature on the relationship between aid and inequality is scarce and contradictory. Most studies are based on dynamic panel data using internal instruments to deal with endogeneity. In addition to these techniques, this article introduces the persistency of inequality and a double-censored Gini index. We apply for the first time a dynamic and double-censored panel data estimated applying the Simulated Maximum Likelihood method to a sample of 18 Latin American countries for 1990-2008. The main findings are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…We found that total aid increases income inequality (column 1, Table 2) showing support for the findings of Ali and Ahmad (2013), Bjørnskov (2010), Gonzalez and Larru (2012), Herzer and Nunnenkamp (2012), and Tezanos et al (2013). However, apart from social aid and multi-sector aid, all the other types of aid have a negative relationship with income inequality, showing that aid to the production sector, economic sector, and humanitarian aid reduce income inequality in the recipient countries.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We found that total aid increases income inequality (column 1, Table 2) showing support for the findings of Ali and Ahmad (2013), Bjørnskov (2010), Gonzalez and Larru (2012), Herzer and Nunnenkamp (2012), and Tezanos et al (2013). However, apart from social aid and multi-sector aid, all the other types of aid have a negative relationship with income inequality, showing that aid to the production sector, economic sector, and humanitarian aid reduce income inequality in the recipient countries.…”
Section: Resultssupporting
confidence: 84%
“…For example, Bjørnskov (2010) for 88 countries over the period 1960-2000 found a positive relationship between aid and inequality in democracies, but in nondemocratic settings, the effect was insignificant. Similarly, Herzer and Nunnenkamp (2012) for 21 countries, Ali and Ahmad (2013) for Pakistan and Gonzalez andLarru (2012), andTezanos et al (2013) for Latin American countries show a positive relationship between foreign aid and income inequality whereas Chong et al (2009) did not find significant relationship for a large pool of countries. Briggs (2017) examine the extent to which foreign aid reaches people at different levels of wealth in Africa, using household surveys to measure the sub-national distribution of a country's population by levels of wealth and by matching this information to data about the location of aid projects from two multilateral donors.…”
Section: Literature Reviewmentioning
confidence: 92%